Penyuluhan Kesehatan Mengenai Bahaya dan Cara Pengolahan Limbah Rumah Tangga di Desa Kalosi Alau, Dua Pitue, Kabupaten Sidenreng Rappang - Mardhatillah Mardhatillah; Sunandar Said; Zulkarnain Sulaiman; Devy Febrianti; Pratiwi Ramlan; Khaeriyah Adri; Syifa Fauziah; Alfiah Syarifuddin; Sofiyah Sofiyah; Mutiara Asysyam; Rizka Magfirah Napa (Universitas Teuku Umar, 2024)
Waste comes from human, animal, and natural activities. Food scraps or wet waste, dry waste, plastic, paper, and so on are types of waste that we often encounter in society. This is a common occurrence in modern-day life. Household waste encompasses waste from various sources such as the kitchen, bathroom, laundry, industrial waste, and human waste. A positive and healthy environment is essential to support human survival. The process of disease is an interaction between disease agents, humans (hosts), and the surrounding environment. The aim of this activity is to provide health information to the public regarding the dangers of household waste and how to manage it through a community approach. The sample for this service was 62 heads of families. Delivery of the material was carried out at the Kalosi Alau Village office through direct practice on how to manage household waste, lectures, and discussions. Wet (organic) waste disposal yielded the highest percentage results, with open trash bins accounting for 77.4%, and closed trash bins accounting for 22.6%. Lack of public knowledge of waste disposal impacts is the cause. We hope that this activity will help the public understand the proper management and utilization of household waste.